2020
DOI: 10.5194/piahs-383-141-2020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting large-scale hydrological variability in a changing environment

Abstract: Abstract. In a context of climate, environmental, ecological and socio-economical changes, understanding and predicting the response of hydrological systems on regional to global spatial scales, and on infra-seasonal to multidecadal time-scales, are major topics that must be considered to tackle the challenge of water resource management sustainability. In this context, a number of strongly-linked key issues need to be addressed by the scientific community, including: (i) identifying climate drivers of hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Closely inter-related key issues and challenges to large-scale hydrology were identified to improve prediction of hydrological systems behavior (surface/sub-surface) on large spatial and time scales (i.e. continental -multidecadal) under changing environmental conditions (Massei et al, 2018;Kingston et al, 2020). Large-scale hydrology depends on interactions across the ocean-atmosphere-vegetation/soil/aquifer system.…”
Section: Euro Friend-watermentioning
confidence: 99%
“…Closely inter-related key issues and challenges to large-scale hydrology were identified to improve prediction of hydrological systems behavior (surface/sub-surface) on large spatial and time scales (i.e. continental -multidecadal) under changing environmental conditions (Massei et al, 2018;Kingston et al, 2020). Large-scale hydrology depends on interactions across the ocean-atmosphere-vegetation/soil/aquifer system.…”
Section: Euro Friend-watermentioning
confidence: 99%
“…Understanding the large-scale hydrological functioning of a hydrosystem is the best approach for grasping a more global view of water reserves and implementing appropriate long-term management strategies (Kingston et al, 2020;Massei et al, 2020). However, this approach requires the construction of a large-scale hydrological model capable of capturing interactions over large areas, while respecting hydraulic continuity across the hydrosystem.…”
Section: Introduction 35mentioning
confidence: 99%
“…Atmospheric circulation patterns play an important role in the formation of runoff and can be a primary source of generative forcing for river systems. Extensive research around the world, including studies in Europe, has demonstrated the influence of different large-scale atmospheric circulation patterns on the climatic characteristics and hydrological behaviour of rivers and lakes [19][20][21][22][23][24][25]. For example, the seasonal variations in dryness and wetness and their links with large-scale atmospheric circulation and global sea surface temperature have been analysed [26].…”
Section: Introductionmentioning
confidence: 99%